2008
DOI: 10.17741/bgsf/80.2.004
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the NH<sub>2</sub> column method for chromium speciation in surface water and soil water

Abstract: A new application of the NH 2 column method has been tested for speciation of Cr(VI) in soil water and surface water. Soil water and surface water samples were collected from two sites near the world's largest stainless steel production plant, Outokumpu Tornio Works, about 10 km south of the City of Tornio, Finland. Dissolved chromium species [Cr(VI) and Cr(III)] were quantified immediately from the water samples with the NH 2 (aminopropylmodified silica) column method and a graphite furnace atomic absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…They also investigated 23 the stability of As species extracted from vegetables and found that the most effective extractant of the three investigated was the protein extraction solution, in which the extracted iAs species were stable for 45 days. It has been shown 24 that Cr VI , in soil water and surface waters, collected from sites near a stainless steel production plant, were stable for three months when stored, prior to acidification and filtration, in either a refrigerator or freezer.…”
Section: Topical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also investigated 23 the stability of As species extracted from vegetables and found that the most effective extractant of the three investigated was the protein extraction solution, in which the extracted iAs species were stable for 45 days. It has been shown 24 that Cr VI , in soil water and surface waters, collected from sites near a stainless steel production plant, were stable for three months when stored, prior to acidification and filtration, in either a refrigerator or freezer.…”
Section: Topical Reviewsmentioning
confidence: 99%
“…For the selective retention of Cr VI the ''NH2'' column 24 which consists of aminopropyl-modified silica has been used. The method was applied to the analysis of surface and soil water.…”
Section: Solid-phase Extractionmentioning
confidence: 99%